Local Government Efforts in Encouraging the Existence of Subsistence Agriculture as an Alternative to the Supply of Food Needs in Lingga Regency - Wijaya, Mendra; Handrisal, Handrisal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
As one of the regions in the Riau Archipelago Province, Lingga Regency has its potential in the agricultural sector, supporting local food needs to distribute the surrounding area. So far, food needs in Lingga are supplied from Jambi Province or other regions, so that the dependence on food from other regions is very high. So, if the weather changes every year, the supply of food needs will decrease, and prices will be higher. The solution, the production of subsistence farmers, can be used as an alternative to meet food needs. Therefore, local governments encourage subsistence agricultural productivity so that production results are utilized by providing subsidies for agricultural production facilities, supporting farming capital, strengthening farmer institutions, and providing rural transportation. Meanwhile, technology cannot increase productivity, considering that subsistence farmers still use traditional culture, so local farmers cannot use that modern agricultural technology. This study aims to determine how local governments encourage the productivity of subsistence farmers as suppliers of regional food needs. Then this research is qualitative with a study approach that examines the government's efforts to encourage subsistence agricultural production.